Design of twisted conjugated molecular systems towards stable multi-colored electrochromic polymers. (December 2020) - Gu, Hua; Xue, Yu; Hu, Faqi; Jian, Nannan; Lin, Kaiwen; Wu, Tao; Liu, Ximei; Xu, Jingkun; Lu, Baoyang
Abstract: Promising advancement of conjugated polymers in electrochromic devices require to design high-performance electrochromic polymers with rich color conversion and long-term stability under cyclic electrical loads. Here we report a new strategy in developing multi-colored electrochromic polymers with good stability via twisted conjugated molecular engineering. A series of twisted hybrid precursors are synthesized by coupling ortho-alkylenedioxybenzenes with EDOT units, and their corresponding polymers are facilely electrosynthesized at relatively low polymerization potentials. The structure-property relationships of such ortho-alkylenedioxybenzene-EDOT hybrid precursors and polymers are systematically elucidated via DFT calculations, spectral, morphological, electrochemical and spectroelectrochemical analysis, etc. We demonstrate that the dihedral angle between ortho-alkylenedioxybenzenes and EDOT moieties can substantially affect the electrochemical and electrochromic properties of polymers. As the dihedral angle and electron cloud density increases, these hybrid polymers display distinct multiple color switching nature and good overall performance including high coloration efficiency (>200 cm 2 C −1 ), decent optical contrast (>45%), fast switching (<1 s), and excellent switching stability (96% of optical contrast after 3500 cycling) under cyclic electrical loads. With these findings, this work will provide novel insights for rational design of stable and highly efficient multi-colored electrochromic polymers. Graphical abstract: Image 1 Highlights: Four twisted o -alkylenedioxybenzene-EDOT precursors were synthesized and electropolymerized. Twisted polymer structures contribute to the multi-color switching nature. o -Alkylenedioxybenzene-EDOT hybrid polymers show excellent electrochromic performances and stability.